Analisis Kontribusi, Efektivitas dan Kenaikan Target Pajak Restoran Terhadap Pendapatan Asli Daerah Provinsi DKI Jakarta Tahun 2015 – 2019 - Sindy Meidiana Dwi Jayanti; Maulana Malik Muhammad (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
In restaurant tax revenue, there are several components that need to be known how the contribution, effectiveness and increase in the restaurant tax target to the regional original income of DKI Jakarta Province. The purpose of this study was to determine the criteria for contribution, effectiveness, and increase in the presentation of restaurant tax targets as a source of PAD for DKI Jakarta Province in 2015 – 2019. The data analysis method used was descriptive qualitative analysis using secondary data. The results of this study indicate that the restaurant tax contribution is included in the "Very Bad". Meanwhile, the effectiveness of hotel tax revenue on the target includes "Very Effective" with an average yield of 100.6% per year. And, the increase in the restaurant tax target in presentation increased by an average of 12.15% per year